The world's fastest CPU and SMP node: Some performance results from the NEC SX-9 - Zeiser, Thomas; Hager, Georg; Wellein, Gerhard (Proceedings of the IEEE International Symposium on Parallel&Distributed Processing 2009, 2009)
Classic vector systems have all but vanished from recent TOP500 lists. Looking at the newly introduced NEC SX-9 series, we benchmark its memory subsystem using the low level vector triad and employ an advanced lattice Boltzmann flow solver kernel to demonstrate that classic vectors still combine excellent performance with a well-established optimization approach. Results for commodity x86-based systems are provided for reference. © 2009 IEEE.
UnivIS-Import:2015-04-16:Pub.2009.tech.IMMD.phleir._thewo